Cytomegalovirus Disease in Children With Acute Lymphoblastic Leukemia in the Nontransplant Setting. Issue 6 (August 2015) - Rahbarimanesh, Aliakbar; Ehsani, Mohammadali; Karahroudi, Maedeh; Rashidi, Armin; Aghajani, Motahareh; Meysami, Alipasha; Shahgholi, Elham; Mehrvar, Azim; Tashvighi, Maryam; Keyvani, Hossein
<x xml:space="preserve">Abstract</x> Cytomegalovirus (CMV) disease in pediatric acute lymphoblastic leukemia in the nontransplant setting is very rare. We report our experience with 4 such cases, and review the literature (n=12). The median age at diagnosis was 10 years and 50% of patients were males. Among the 11 cases with available information at the time of diagnosis, CMV disease occurred during maintenance therapy in 10 patients. Fever was present in 9 cases. CMV disease manifested as retinitis in 6, hepatosplenic disease in 3, pneumonitis in 1, and hemophagocytic lymphohistiocytosis in 1 patient. One patient had both CMV retinitis and CMV-related hemophagocytic lymphohistiocytosis. Four of the 7 patients with retinitis complained of visual disturbance at diagnosis. CMV viremia was present in 10 patients. Three patients had at least 1 relapse and developed permanent visual defects, and 1 patient developed recurrent retinal detachment. In conclusion, prolonged immunosuppression is the major etiology and retinitis is the most common manifestation of CMV disease. As a significant number of patients with retinitis are asymptomatic, early diagnosis and treatment is important to prevent permanent visual loss.